Coach authentic leadership connected with performance satisfaction and psychological well-being of team: The mediating role of team cohesion and psychological capital - Zhihua Ruan, Wenhua Liu (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
In today’s world, the psychology of sports and exercise is a crucial factor to study for attaining the higher performance and productivity of athletes. The purpose of the current work is to examine the effect of authentic leadership on team performance satisfaction and psychological well-being. Moreover, the nucleus aim of the current study is to investigate the effect of authentic leadership, performance satisfaction, psychological well-being, while mediating by team cohesion and psychological capital. There is a growing indication ascertaining the positive effects of sport and exercise leaders engaging in authentic leadership. However, researchers have limited knowledge of how authentic leadership is related with athletes’ performance satisfaction and psychological well-being, the supporting system(s) that illuminate such associations, and modifications in relationships within a sports sector. The data is accumulated through administrated a survey questionnaire, it is more as a suitable method to generate under present study because it will give accurate data on numerical figure bases that can be valued certainly and that is free from any type of the ambiguities. The simple random sampling technique is used under this study for selecting the sample from large population. By using simple random sampling technique, the questionnaire is administered to distributed among 250 female athletes of different team groups in China. Out of from 250 questionnaires, 200 questionnaires were received back from athletes. The nature of the study is cross sectional as only one- time data is collected from athletes. This study used the Smart PLS software for analyzing the relationship among variables such as authentic leadership, performance satisfaction, psychological well-being, team cohesion and psychological capital. The outcome of the study reveals that authentic leadership has a significant and positive relationship with performance satisfaction and psychological well-being of the team players. Further, the psychological capital and team cohesion enhances the team performance satisfaction and psychological well-being. However, at the end, future limitations for further studies, practical implications for athlete practitioner, coach and policy- makers are provided at the end of the study.